Isolated Fallopian Tube Torsion after Eating Origan and Fennel during Pregnancy - Farahnaz Sadat Ahmadi; Fariba Yarandi; Shamin Alaghi; Azizeh Ghaseminejad; Soleiman Abbasi (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2015)
Background: Isolated fallopian tube torsion is very rare during pregnancy .The reporter's show that the right fallopian tube torsion is most common. Most of the cases have presented in the third trimester. The diagnosis of this torsion is very difficult. There are not pathognomonic symptoms; clinical, imaging, or laboratory findings. The diagnosis is proved during the operation.  Case presentation: A 29 years old G4P3L2D1RIII, 33weeks pregnant woman presented with acute colicky abdominal pain with 4 episodes of vomiting &nausea. The sonogram revealed a 2 cm exophytic mass of left ovary probably is haemorrhagic cyst.  A laparotomy was performed. The ovaries were normal and there was the isolated torsion in left tube with congestion and necrose. Cesarean section and salpingectomy was performed. Conclusion: Although isolated twisted fallopian tube during pregnancy is very rare, we should Pay attention in the differential diagnosis of acute abdomen in pregnancy for this case. Early surgical intervention will decrease obstetric morbidity and may help us to preserve the fallopian tube.